Правовий компроміс і правовий конфлікт як ціннісні виміри права - Бобровник, С.В. (Альманах права, 2012)
Аналізуються наукові підходи до характеристики компромісу і конфлікту у праві. Обґрунтовується авторське бачення цих категорій та їх ознак як ціннісних вимірів права. Анализируються научные подходы к характеристике компромисса и конфликта в праве. Обоснованавторский взгляд на эти категории, их черты как ценностных измерений права. It examines scientific approaches to the determination of legal conflict in broad as well as in narrow sense. It also substantiates author’s determination of legal conflict as bilateral contacts of subjects, based on legal contradictions which are characterized by violation or obstruction in realization of their interests and leads to the crisis in social relations. It has been investigated the characteristic features of legal conflict which draw a boundary between this category and other conflicts that occur in society. It has been revealed the features of legal compromise according to its functional direction as well as instrumental significance in regulation of social conflicts. The legal compromise is defined as mediated by legal norms value oriented means of conflict regulation (inter alia legal conflict), based on mutual concessions of the participants of social relations. The purpose and result of its functioning is the state of social agreement and binding democratic values in society. It has been determined the peculiarities of inner and outer levels of legal compromise and conflict.